Modified Zhibai Dihuang pill alleviated urinary tract infection induced by extended-spectrum β-lactamase Escherichia coli in rats by regulating biofilm formation - Kaifa Chen; Yongsheng Zhu; Hongwei Su; Hao Jiang; Xin Liu (Taylor & Francis Group, 2023)
AbstractContext Zhibai Dihuang pill (ZD), a traditional Chinese medicine nourishes Yin and reduces internal heat, is believed to have therapeutic effects on urinary tract infections (UTIs).Objective To explore the effects and mechanism of modified ZD (MZD) on UTI induced by extended-spectrum β-lactamase (ESBLs) Escherichia coli.Materials and methods Thirty Sprague-Dawley rats were randomly divided into control, model (0.5 mL 1.5 × 108 CFU/mL ESBLs E. coli), MZD (20 g/kg MZD), LVFX (0.025 g/kg LVFX), and MZD + LVFX groups (20 g/kg MZD + 0.025 g/kg LVFX), n = 6. After 14 days of treatment, serum biochemical indicators, renal function indicators, bladder and renal histopathology, and urine bacterial counts in rats were determined. Additionally, the effects of MZD on ESBLs E. coli biofilm formation and related gene expression were analyzed.Results MZD significantly decreased the count of white blood cells (from 13.12 to 9.13), the proportion of neutrophils (from 43.53 to 23.18), C-reactive protein (from 13.21 to 9.71), serum creatinine (from 35.78 to 30.15), and urea nitrogen (from 12.56 to 10.15), relieved the inflammation and fibrosis of bladder and kidney tissues, and reduced the number of bacteria in urine (from 2174 to 559). In addition, MZD inhibited the formation of ESBLs E. coli biofilms (2.04-fold) and decreased the gene expressions of luxS, pfS and ompA (1.41-1.62-fold).Discussion and conclusion MZD treated ESBLs E. coli-induced UTI inhibited biofilm formation, providing a theoretical basis for the clinical application of MZD. Further study on the clinical effect of MZD may provide a novel therapy option for UTI.